"It is good to take her early to the doctor" - mothers' understanding of childhood pneumonia symptoms and health care seeking in Kilimanjaro region, Tanzania - Florida Muro; Judith Meta; Jenny Renju; Adiel Mushi; Hilda Mbakilwa; Raimos Olomi; Hugh Reyburn; Helena Hildenwall (BMC, 2017)
Abstract Background Pneumonia is among the leading causes of avoidable deaths for young children globally. The main burden of mortality falls on children from poor and rural families who are less likely to obtain the treatment they need, highlighting inequities in access to effective care and treatment. Caretakers' illness perceptions and care-seeking practices are of major importance for children with pneumonia to receive adequate care. This study qualitatively explores the caretaker concepts of childhood pneumonia in relation to treatment seeking behaviour and health worker management in Moshi urban district, Tanzania. Methods In May - July 2013 data was gathered through different qualitative data collection techniques including five focus group discussions (FGDs) with mothers of children under-five years of age. The FGDs involved free listing of pneumonia symptoms and video presentations of children with respiratory symptoms done, these were triangulated with ten case narratives with mothers of children admitted with pneumonia and eleven in-depth interviews with hospital health workers. Transcripts were coded and analysed using qualitative content analysis. Results Mothers demonstrated good awareness of common childhood illnesses including pneumonia, which was often associated with symptoms such as cough, flu, chest tightness, fever, and difficulty in breathing. Mothers had mixed views on causative factors and treatments options but generally preferred modern medicine for persisting and severe symptoms. However, all respondent reported access to health facilities as a barrier to care, associated with transport, personal safety and economic constraints. Conclusion Local illness concepts and traditional treatment options did not constitute barriers to care for pneumonia symptoms. Poor access to health facilities was the main barrier. Decentralisation of care through community health workers may improve access to care but needs to be combined with strengthened referral systems and accessible hospital care for those in need.